2017
DOI: 10.21010/ajtcam.v14i2.19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibacterial, Antitumor, Antioxidant Activities and Phenolic Constituents of Field-Grown and in Vitro-Grown Lysimachia Vulgaris L.

Abstract: Background: Lysimachia vulgaris L. (Yellow loosestrife) is a medicinal plant in the family Myrsinaceae. It has been used in the treatment of fever, ulcer, diarrhea and wounds in folk medicine. It has also analgesic, expectorant, astringent and antiinflammatory activities. Two different sources of the plant (field-grown and in vitro-grown) were used to evaluate the biological activities (antibacterial, antitumor and antioxidant) of L. vulgaris. In vitro-grown plant materials were collected from L. vulgaris plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…HO-1 , which is an antioxidant-responsive gene regulated by Nrf2, degrades heme to generate ferrous ion, CO, and biliverdin, all of which are related to the reduction of ROS [ 29 ]. In addition, few studies have reported the antioxidative activity of LV extract [ 12 , 13 ]. Consistent with these findings, we found that liver Nrf2 and HO-1 protein levels in LYS group were significantly increased, indicating that the extract regulates the Nrf2 activator within the cellular system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HO-1 , which is an antioxidant-responsive gene regulated by Nrf2, degrades heme to generate ferrous ion, CO, and biliverdin, all of which are related to the reduction of ROS [ 29 ]. In addition, few studies have reported the antioxidative activity of LV extract [ 12 , 13 ]. Consistent with these findings, we found that liver Nrf2 and HO-1 protein levels in LYS group were significantly increased, indicating that the extract regulates the Nrf2 activator within the cellular system.…”
Section: Discussionmentioning
confidence: 99%
“…davurica (LV), also known as the yellow loosestrife, is a medicinal plant that is well known for treating ulcers, fever, inflammation, and diarrhea [ 11 ]. Recent findings have revealed that LV also has antifungal, antibacterial, antitumor, and antioxidative activities [ 12 , 13 ]. Moreover, LV is a non-toxic, edible plant that grows in Europe, North America, and Asian countries and is registered as a food ingredient in the Korean Food Standards Codex [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal effectiveness of these secondary metabolites and their antimicrobial activity and exhibited mechanisms are not fully understood, although specific studies attempted to decipher the mechanism(s) involved. While alkaloids are microbicidal (Ghoshal et al 1996), phenolic compounds such as flavones were inhibitory to the growth of A. niger and C. albicans and B. subtilis, E. coli, and S. epidermidis (Rahua et al 2000). The mode(s) of action of flavonoids is related to the formation of complexes with extracellular soluble protein and bacterial cell walls (Gorniak et al 2019) and inhibition of DNA gyrase and β-hydroxy-acyl carrier with protein dehydrogenase activity (Tsuchiya et al 1996;Cushine and Lamb 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Total phenolic content was analyzed using Folin-Ciocalteu colorimetric method with modification according to Yildirim et al [20]. Briefly, 20 µl of crude extract at a 1 mg/ml concentration was added to a 96-well flat-bottomed plate, and 100 µl of tenfold diluted 2M Folin-Ciocalteu's reagent was added into each well.…”
Section: Determination Of Total Phenolic Contentmentioning
confidence: 99%